Nutrition and Health Promotion pada Obesitas : Literature Review - Fahrurozi, Muhammad; Aristyarini, Indrawati (Jurnal Ilmiah Kesehatan, 2017)
Background: Primary school children (6-12 years old) have many characteristics of physical activity. Therefore, at this time children need high energy to support their activities. The purpose of this literature review is to know the evidence-based obesity and methods used in overcoming obesity problems in school-aged children. Method: Literature review method is used in this research. Journal is assesed by used the keywords and had found 92 article then was extracted 10 article that relevan by the author. Results: The problem of obesity is influenced by several factors including: age, gender, socioeconomic status, geographical condition, history of nutritional intake. Impacts that can occur if obesity is not handled properly include the occurrence of cardiovascular, endocrine, musculoskeletal and gastrointestinal complications, and may have psychosocial consequences. Activity and rest is needed to support in the prevention of obesity. Keywords: Nutrition of children, obesity and health promotion.